9, 10-Di(hydroxymethylphenyl)anthracenes: Highly efficient triplet annihilators with small singlet-triplet energy gap (ΔEST) and planar configuration. (May 2020) - Yu, Xue; Fan, Congbin; Dai, Guoliang; Wang, Xiaomei; Ye, Changqing; Tao, Xutang
Abstract: A series of 9, 10- di (hydroxymethylphenyl)anthracene chromophores (named as E - o -DHMPA, Z - o -DHMPA, m -DHMPA and p- DHMPA ) are designed to tailor triplet-triplet annihilation upconversion through isomer engineering. It was found that improving molecular planarity makes for molecular π-π interaction, meanwhile, molecular excited singlet energy level ( E S1 ) shows decreasing; however, the triple energy level ( E T1 ) exhibits almost equal. Thus, small singlet-triplet energy gap ( ΔE ST ) of chromophores could be designed. Selective excitation of sensitizer (palladium II tetrabromophenylporphyrin, PdBrTPP) in solution containing annihilator results in the upconversion (UC) efficiency ( Φ UC ) increasing from E - o -DHMPA (15.9%), Z- o- DHMPA (18.7%), m -DHMPA (26.0%) to p -DHMPA (26.8%), accompanied by the excitation threshold intensity ( I th, mW⋅cm −2 ) decreasing from E - o -DHMPA (292.74), Z- o- DHMPA (174.41), m -DHMPA (36.58) to p -DHMPA (29.78), which are in agreement with the ΔE ST decreasing and planarity improving of these isomers. Annihilator with small energy gap ( ΔE ST ) and planar configurtion has contribution to triplet-triplet annihilation (TTA), supported by the fact of the I th value reducing, and thereby increasing UC efficiency ( Φ UC ), which provides a new strategy for molecule design to develop new triplet annihilator. Finally, the TTA-UC powered photolysis of bilirubin was conducted for the first time, suggesting that TTA-UC can act as an effective light source used in the light therapy for neonatal hyperbilirubinemia. Highlights: Triplet annihilator with small excited singlet-triplet energy gap was designed. Annihilator with small energy-gap and planar exhibit efficient TTA-UC efficiency. Efficient UC blue-light could be suitable light-source used in the light therapy.